PENGARUH SENAM DIABETIK TERHADAP PENURUNAN KADAR GULA DARAH PADA PASIEN DM TIPE 2 DI PUSKESMAS WONOGIRI 2. - Nugroho, Yohanes Wahyu (Jurnal AKPER GSH, 2019)
Data from the International Diabetes Federation (IDF), the global prevalence rate of type II DM sufferers in 2013 amounted to 382 million cases, in 2013 diabetes mellitus was 387 million cases and in 2035 the number of DM type II DM incidents will increase to 55% (592 million) among DM sufferers aged 40-59 years. The purpose of this study was to determine the effect of diabetic exercise on reducing blood sugar levels of type 2 in type II diabetes mellitus sufferers in the working area of Puskesmas Wonogiri 2. This type of research is a pre-experiment using a one group pre-post test design approach. The sample in this study was the random selection of elderly people with type 2 diabetes mellitus with a total of 10 respondents, both male and female, using purposive sampling technique. The data collection tool used was a checklist sheet. The analysis used in this study was univariate and bivariate analysis. The results of the study showed that the effect of giving diabetic exercise on reducing blood sugar levels in the work area of the Wonogiri 2 Community Health Center in 2019 with a p value of 0.000.Objective : It is expected for respondents to always maintain a diet so that blood sugar levels remain within normal limits and for people with Type II DM to regularly do diabetic exercises to reduce blood sugar levels.This type of research uses a pre-experimental method with a one group pretest-posttest design. This design also does not have a control group, the design is carried out by observing 2 times, namely before and after being given action (Notoatmodjo, 2010). : Data analysis using t test. The results showed that diabetes exercise was effective in reducing blood glucose levels in patients with type II diabetes in the working area of Puskesmas Wonogiri 2 with a p value of 0.000.Keywords : diabetes mellitus type 2, diabetes gymnastics.